1993
DOI: 10.3109/00365529309096062
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Release in Response to Gut Injury

Abstract: We evaluated nitric oxide release in several models of intestinal inflammation through luminal nitrite concentrations. In anesthetized rabbits, piglets, and guinea pigs, luminal lavages were collected from loops of normal or injured small intestine. Lavages were analyzed spectrophotometrically for nitrite (Griess reagent) and protein. Myeloperoxidase (MPO) content of intestinal segments was used as an index of granulocyte infiltration and intestinal inflammation. Acute ileal inflammation was induced by luminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…Corresponding with these results, castoroil-induced diarrhoea was prevented by administration of NO-synthase-inhibitors in an in vivo study (Mascolo et al, 1993). Conversely, inhibition of NO-synthase in vivo resulted in gastric and duodenal HCO3- (Takeuchi et al, 1993) and intestinal fluid secretion (Mourad et al, 1993;Miller et al, 1993a,b) and in an enhancement of intestinal epithelial permeability (Kubes, 1992;Miller et al, 1993c), thus pointing towards an antisecretory and/or proabsorptive role of NO in the intestine.…”
Section: Introductionmentioning
confidence: 50%
“…Corresponding with these results, castoroil-induced diarrhoea was prevented by administration of NO-synthase-inhibitors in an in vivo study (Mascolo et al, 1993). Conversely, inhibition of NO-synthase in vivo resulted in gastric and duodenal HCO3- (Takeuchi et al, 1993) and intestinal fluid secretion (Mourad et al, 1993;Miller et al, 1993a,b) and in an enhancement of intestinal epithelial permeability (Kubes, 1992;Miller et al, 1993c), thus pointing towards an antisecretory and/or proabsorptive role of NO in the intestine.…”
Section: Introductionmentioning
confidence: 50%
“…One possible mechanism could be the decreased perfusion of the small intestine because it has been shown that hypoxia induced by low flow conditions augments proinflammatory cytokine release from the liver and gut. [24][25][26][27][28] Moreover, preliminary results indicate that splenic and peritoneal macrophages from rats subjected to hypoxia express iNOS and release a large amount of NO 3 − /NO 2 − . Thus, the decreased blood flow in the liver, small intestine, and spleen after hemorrhage, as demonstrated in the present study (Table 2), may induce a local increase of cytokines that could, in turn, up-regulate iNOS expression, leading to a prolonged increase in tissue and plasma levels of NO 3 − /NO 2 − .…”
Section: Discussionmentioning
confidence: 99%
“…After deproteinization, the total nitrite concentration was measured spectrophotometrically by the Griess reaction. 14 According to the method of Miller et al, 15 no attempt was made to convert the nitrate levels to nitrite to avoid any technical errors that may accompany the nitrate conversion process.…”
Section: Methodsmentioning
confidence: 99%